Flipbook food chain in an ecosystem to improve learning outcomes in elementary school - Hariyastuti, Anik; Wardani, Sri; Raharjo, Tri Joko; Subali, Bambang; Widiarti, Nuni (Jurnal Ilmiah Pendidikan Dasar, 2024)
The lack of ability of teachers to develop technology-based learning media and low interaction with learning tasks negatively affect students' learning outcomes. The study aims to determine the feasibility and effectiveness of a web-based Fiborampae (Flip Book Food Chain in Ecosystems) course on IPAS material. The research method used is the RnD model Borg and Gall which consists of several stages, namely: potential and problems;  data collection; product design; design validation; design revision; product trials; product revision; trial use in which the data collection methods include questionnaires and test. Based on the validation team's assessment, Fiborampae media is included in the most appropriate category, which is also a finding in this research. The evaluation results for the content were 93%, and the media factor was 90.8%. The results of the N-Gain test on the pre-and post-test values showed a mean difference of 0.739 under a moderate criterion and an effectiveness value of 73.95 under a highly effective definition. Meanwhile, the reference category reached a value of 0.425 under moderate criteria and had an efficiency of 42.35 under the low-efficiency definition. The interpretation of the data shows that classrooms using Fiborampae media achieve higher learning outcomes with more effective standards. The implications of this research are expected to apply this medium to simpler devices with a simple and attractive appearance that can be used in various teaching situations and support character development within the new curriculum.